Reconstruction of Criminal Policy in Combating Crimes of Disinformation and Hate Speech in the Digital Space - Endah Safitri (Eduvest - Journal of Universal Studies, 2026)
The development of digital technology has brought an ambivalent impact on Indonesia’s criminal justice system. On one hand, advancements in information technology have expanded the space for public expression and the democratization of information; on the other hand, various forms of misuse have emerged, such as the dissemination of disinformation (hoaxes) and hate speech, which threaten public order and social cohesion. This study aims to examine the urgency of reconstructing criminal policy in combating disinformation and hate speech crimes in the digital space and to formulate policy strategies that can balance the protection of public order with the guarantee of freedom of expression. This article examines the urgency of reconstructing criminal policy in addressing such crimes through a normative–critical approach. The analysis reveals that current criminal policies—particularly under the Electronic Information and Transactions Law (UU ITE) and the 2023 National Criminal Code (KUHP)—remain predominantly repressive and fail to prioritize proportionality, communicative justice, and human-rights protection. A reconstruction of criminal policy is therefore required to balance the need to maintain public order with the guarantee of freedom of expression in digital spaces. This reconstruction should be oriented toward restorative justice, legal transparency, and digital literacy as integral components of a socially just approach to combating cybercrime.